Sample learning modules in communication arts for grade six learners of elementary science - De la Peña, Betty A. 1949- (1977)
These sample Learning Modules in Communication Arts for Grade Six Learners of Elementary Science are intended as self-instructional materials. Materials are based on rhetorical facts rather than on the linguistic elements and vocabulary items. The materials integrated the four language skills: listening, speaking, reading, and writing. Statistical data based on the results of the pre- and post- tests showed that there was positive learning due to the use of the modularized materials.